On the occurrence and strength of multi-frequency multi-GNSS Ionospheric Scintillations in Indian sector during declining phase of solar cycle 24 - Srinivasu, V. K. D.; Dashora, N.; Prasad, D.S.V.V.D.; Niranjan, K.; Krishna, S. Gopi (My University, 2017)
This study presents unique perspectives of occurrence and strength of low latitude ionospheric scintillations on multiple signals of Global Navigation Satellite System (GNSS) and its frequency dependence using continuous observation records of 780 nights. A robust comparative analysis is performed using scintillation index, S4 and its variation during pre-midnight and post-midnight duration from a GNSS receiver located at Waltair (17.7 N, 83.3 E), India, covering period from July 2014 to August 2016. The results, generally exhibit the impact of declining phase of solar cycle 24 on occurrence and strength of scintillations, which, however, is evidently different over different frequencies transmitted from different GNSS systems. A deeper quantitative analysis uniquely reveals that apart from the solar cycle and seasonal effects, the number of visible satellites of a selected GNSS markedly affect the occurrence and also the strength. Processing scheme of adopting 6 hourly time windows of pre-midnight and post-midnight brought a novel result that the strength and occurrence of strong scintillations decrease with declining solar activity during pre-midnight hours but remarkably increase for moderate and weak scintillations during post-midnight. The physical processes that dominate the post-midnight equatorial ionosphere are invoked to explain such variations that are special during declining solar activity. Finally, inter-GNSS signal analysis in terms of the effect of strong, moderate and weak scintillations is presented with due consideration of number of satellite passes affected and frequency dependence of mean S4. The quantitative results of this study emphasize for the first time effect of low latitude scintillation on GNSS signals in Indian zone under changing background solar and seasonal conditions.
Keywords: Ionospheric irregularities; Solar Cycle; Global navigation satellite system; Morphology of scintillations; Equatorial and low latitude; Radio wave dispersion; Multi-frequency scintillations